2015
DOI: 10.1111/febs.13341
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric assembly is required for chaperone activity of the filamentous γ‐prefoldin

Abstract: Prefoldins (PFDs) are molecular chaperones with a distinctive jellyfishshape that have a general role in de novo protein folding in Archaea and in the biogenesis of cytoskeleton proteins in eukaryotes. In general, PFDs are hetero-hexameric protein assemblies consisting of two a and four b subunits. However, a PFD variant called gamma-prefoldin (cPFD), isolated from the hyperthermophilic archaeon Methanocaldococcus jannaschii, exhibits a unique filamentous structure that is composed of hundreds of monomeric sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 28 publications
5
54
1
Order By: Relevance
“…The connectors were assembled with γPFD in a controlled manner by first denaturing the proteins in 8 M guanidinium-HCl and combining the proteins in various molar ratios, followed by rapid dilution and refolding in an aqueous buffer. The propensity of the connectors to attach to γPFD subunits and extend filaments was confirmed using a protein–protein interaction pull-down assay 11 ( Supplementary Fig. 4 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The connectors were assembled with γPFD in a controlled manner by first denaturing the proteins in 8 M guanidinium-HCl and combining the proteins in various molar ratios, followed by rapid dilution and refolding in an aqueous buffer. The propensity of the connectors to attach to γPFD subunits and extend filaments was confirmed using a protein–protein interaction pull-down assay 11 ( Supplementary Fig. 4 ).…”
Section: Resultsmentioning
confidence: 91%
“…Importantly, the interface between each γPFD subunit is pliant and amenable to structural modification 9 ; the β-sheet oligomerization domains and the coiled-coils of the subunits are physically separate and can be modified independently for expanded function 10 ; and the assembled filament is extremely stable to thermal and solvent-induced denaturation 8 . The inherent molecular chaperone function of the filament 11 may also serve to stabilize and re-activate enzymes in denaturing conditions such as during production of composite materials and enzyme–nanomaterial conjugates. Furthermore, progress has been made to gain control over γPFD filament elongation through the creation of a capping protein called TERM (thermophilic extension resistant mutant) to control filament length 9 .…”
mentioning
confidence: 99%
“…We have shown previously that γ‐PFD can interact with a broad range of non‐native proteins to capture and stabilize them using its coiled coil domains, and that filamentous assembly is required for such activity . Thus, it is possible that γ‐PFD–SpyTag interacts with the attached enzymes in a similar manner to provide favorable conditions for their catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…One structural aspect of sHsps that likely contributes to their chaperone activity is their dynamic oligomerization. Many previous studies have suggested that both the oligomerization dynamics in addition to sequences of the chaperone that act as “interacting sites” contribute to the activity of sHsps . Since oligomerization implies potential multivalent protein architectures, we were interested in developing a chemical system to mimic potential oligomeric states that sHsps can assume.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have suggested that both the oligomerization dynamics in addition to sequences of the chaperone that act as "interacting sites" contribute to the activity of sHsps. 20,61,62 Since oligomerization implies potential multivalent protein architectures, we were interested in developing a chemical system to mimic potential oligomeric states that sHsps can assume. Our rationale is that this would allow for evaluation of multivalent effects on chaperone activity of sHsps in the absence of the dynamic properties of the native system, which currently leads to indeterminate results.…”
Section: Chaperone Activity Of B1ntr-conjugated Nanoparticlesmentioning
confidence: 99%